Analisis Kebijakan Indonesia Terkait Emisi Karbon Melalui Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA) - Lasut, Eugenie Brigita; Nau, Novriest Umbu Walangara; Seba, Roberto Octavianus Cornelis (Fakultas Ilmu Sosial dan Hukum, 2024)
Climate change is an international issue and a concern of many countries especially Indonesia. The growth and development of mobility in the aviation sector is one of the causes of air pollution produced by aircraft carbon emissions. Indonesia decided to a make policies through the Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA) program initiated by the International Civil Aviation Organization (ICAO) to reduce and solve the problem of carbon emissions in the aviation industry. This study applies a descriptive qualitative method that describes the results of the research in a narrative based on data collected using a literature study. This study will also analysed Indonesia’s policies for carbon emissions through Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA) with the theory of Neoliberal Institutionalism which considers that the state is not the only actor and international organizations also play a role as an actor that create the complex interdependence. This study explain that Indonesia's policies for carbon emissions in the aviation sector are a development of previous policies for climate change using a Paris Agreement.